Desempenho produtivo e qualidade da carne de ovinos terminados em pastagem irrigada no semiárido nordestino. - FERNANDES JÚNIOR, G. A. (2010)
Resumo: A realização do diagnóstico teve por objetivo conhecer os sistemas de produção, tipificar os produtores cooperados da COOPAMNU; identificar problemas; e estreitar as relações da Embrapa com a cooperativa e os técnicos que atuam na região. As atividades do subprojeto em questão, iniciaram-se no final de 1996 com a obtenção de dados secundários sobre os polos agropecuários do estado e a escolha da região para as atividades de intervenção. Posteriormente foram coletados mais dados enfocando a região selecionada (Ouro Preto do Oeste, região central do estado e sua maior bacia leiteira) dando ênfase aos dados referentes as organizações sociais rurais. Em abril de 1997 foram realizadas reuniões com orgãos locais de assistência técnica e fomento, visitas aos principais laticínios do município e finalmente visita as sete organizações ligadas a pecuária leiteira com maior potencial para desenvolver o subprojeto. Destas, a COOPAMNU foi escolhida para dar inicio ao trabalho. Na escolha, foram levados em conta os seguintes critérios: tempo de existência da entidade; número de projetos de financiamentos; número de sócios efetivos; localização; representatividade dos associados em relação a média dos produtores da região; assistência técnica recebida; parcerias existentes com orgãos como a própria Embrapa, prefeitura municipal, etc.; interesse demostrado pelos associados; e a impressão do grupo de trabalho no contato direto através das palestras promovidas nas sedes das associações. [Productive performance and meat quality of sheep finished in irrigated pasture in the northeastern semi arid]. Abstract: The aim of this study was to evaluate the productive performance and meat quality of animals of Santa Inês (SI), Somalis Brasileira (SO) and Morada Nova (MN) breeds and ½ Dorper x ½ Morada Nova crossbreds (F1) finished in irrigated cultivated pasture. Breeding season was done simultaneously for SI, SO and MN breeds and half of the Morada Nova females was crossed with Dorper rams. In lambing phase, ewes and lambs were raised in native pasture. After weaning, thirty-three males lambs (thirteen Santa Inês, seven Somalis Brasileira, six Morada Nova and seven F1) were selected to be finished in irrigated cultivated pasture. The animals were housed in paddocks of Panicum maximum cv. Tanzania on a rotational system in a randomized design. Each week the animals were weighed and evaluated for body condition score (ECC), FAMACHA © degree, number of eggs per gram of faeces (OPG), packed cell volume (VG) and total plasma protein (PPT). At the end of the field trial the animals were slaughtered and evaluated for quantitative and qualitative traits of carcass and commercial cuts, as well as qualitative aspects of meat. Statistical analyses were performed by SAS software using the GLM procedure. The Morada Nova breed presented lower variation in the values of VG and FAMACHA © over time even with the highest peak of OPG, indicating this breed as more resilient to helminthic natural infection. For carcass traits Somalis Brasileira breed showed the best hot and cold carcass dressing and the greatest finishing degree. Genetic groups Santa Inês and F1 showed a better carcass conformation. AOL was similar between Santa Inês, Somalis 17 Brasileira and F1, the latter being also similar to Morada Nova. Considering the compactness indexes for body, carcass and leg, Santa Inês, Somalis and Brazilian F1 group were similar showing greater specialization for meat production. It can be concluded that for the conditions of management employed in this study, the genotypes ranged their performances in relation to traits evaluated, since no group was superior or inferior for all traits, which shows that all groups can be improved. Good meat quality characteristics presented by genetic groups Santa Inês, Morad Nova and Somalis Brasileira, and the crossbreed ½ Dorper x ½ Morada Nova, make them excellent choices to fill a more demanding market, with no significant differences between them.